2015
DOI: 10.1002/cmdc.201500025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Antiproliferative Activity of Amido and Amino Analogues of the Marine Alkaloid Isogranulatimide

Abstract: Marine organisms have proven to be a promising source of new compounds with activity against tumor cell lines. Granulatimide and isogranulatimide are marine alkaloids that have been shown to inhibit checkpoint kinase 1 (Chk1), a key protein in the DNA damage response and an emerging target for anticancer therapeutics. Here, we describe the synthesis and preliminary evaluation of amido and amino analogues of isogranulatimide. The new derivatives were prepared in three steps from 2-imidazol-1-yl-1H-indol-5-ylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…These biomarkers, associated with epithelial-derived cell lines and also some colorectal, breast and lung cell lines, could be of use in predicting the likelihood of patient response to didemnin B or analogues in a therapeutic setting. Synthetic analogues related to the polyandrocarpamines 955 were found to be inhibitors of H 2 S production by cystathionine beta-synthase, 956 and SAR studies have been reported for thiaplidiaquinones A and B 957 (various biological targets), 958 cadiolides A-C 959,960 (antibacterial), 961,962 rubrolides 963 (photosynthesis inhibitors), 964 meridianins 965 (antimalarial and antituberculosis), 966 isogranulatimide 967 (cytotoxicity), 968 and lamellarins 969 (cytotoxicity). 970…”
Section: Molluscsmentioning
confidence: 99%
“…These biomarkers, associated with epithelial-derived cell lines and also some colorectal, breast and lung cell lines, could be of use in predicting the likelihood of patient response to didemnin B or analogues in a therapeutic setting. Synthetic analogues related to the polyandrocarpamines 955 were found to be inhibitors of H 2 S production by cystathionine beta-synthase, 956 and SAR studies have been reported for thiaplidiaquinones A and B 957 (various biological targets), 958 cadiolides A-C 959,960 (antibacterial), 961,962 rubrolides 963 (photosynthesis inhibitors), 964 meridianins 965 (antimalarial and antituberculosis), 966 isogranulatimide 967 (cytotoxicity), 968 and lamellarins 969 (cytotoxicity). 970…”
Section: Molluscsmentioning
confidence: 99%
“…A molecular docking based study was used to design potential new specific Chk1 inhibitors [ 161 ]. The same group also synthesized new amino or amido substituted analogs based on the granulatimide/isogranulatimide framework and examined their biological activity [ 162 ]. Two of the new compounds (where ring C is opened) were more potent than the parent compounds in inhibition of cell growth with IC 50 values in the low micromolar range.…”
Section: Ascidian Compounds Affecting Signaling Pathwaysmentioning
confidence: 99%
“…Marine microorganisms have attracted great attention since they have developed unique metabolic and physiological capabilities that not only ensure survival in extreme habitats but also offer the potential to produce compounds with antitumor and other interesting pharmacological activities that would not be observed in terrestrial microorganisms [ 10 , 11 , 12 ]. Recently, several synthetic analogues with a promising anti-proliferative activity are reported [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%